Identification of Natural Recharge Characteristics Based on Time-Lapse Microgravity Data for Sustainability Utilization at Lahendong Geothermal Field, Indonesia - Agung, Lendriadi; Syamsu Rosid, Mohammad; Tofan Sastranegara, Mochamad; Lolla Riandari, Baiq (Geological Agency, 2026)
The sustainable utilization of geothermal resources heavily relies on maintaining the fluid mass balance within the reservoir. Excessive fluid extraction without sufficient natural recharge can cause significant declines in reservoir pressure, thus threatening the long-term sustainability of geothermal energy production. This study specifically addresses the challenge of accurately characterizing natural recharge dynamics in the Lahendong Geothermal Field, where ongoing exploitation activities have led to considerable fluid mass deficits. To tackle this issue, time-lapse microgravity monitoring was conducted annually from 2015 to 2023 across 118 gravity benchmark stations strategically distributed throughout the reservoir area. The collected microgravity data were analyzed using Gauss's theorem to quantify the changes in reservoir mass balance over time. The calculated reservoir mass changes based on microgravity data were validated against mass balance estimates derived from actual well flow rate measurements. The findings indicate that natural recharge in Lahendong varies significantly, ranging from 0 to 3 M ton/year, exhibiting a clear cyclical pattern with approximately three-year intervals. On the average, natural recharge supplies approximately 1 M ton/year to the reservoir. The results validate time-lapse microgravity monitoring as a robust tool for detecting reservoir mass changes, offering critical insights into adaptive fluid injection strategies.